Deixis in Taylor Swift’s Speech at New York University Spring Graduation 2022: A Pragmatics Study - Amalin Solihat Lestari; Ervina C M Simatupang (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
The study purposes to analyse deixis types in speech conducted by Taylor Swift in particular event, and the factors of the deixis on its data source. It implemented qualitative descriptive method with the theory from Sutopo (2006). Theories used in the research are regarding to deixis from Cruse (2000), and Levinson (1983). For the factor of deixis, the writer used the theories from Cruse (2000), and Levinson (1989). The results of the research indicated (1) there are 51 data of five deixis types found in Taylor Swift’s Speech at New York University Spring Graduation 2022, consisting of: 6 data (11.7%) of person deixis, 5 data (9.8%) of place deixis, 6 data (11.7%) of time deixis, 1 data (1.9%) of discourse deixis, and 33 data (64.7%) of social deixis. (2) The data analysis revealed five factors that influence the use of deixis: participant role, usage function, social status, formality/informality, and intimacy. By examining patterns and variations in these aspects of deixis, the study contributes to our understanding of how speakers utilize deixis to establish referential coherence and navigate spatial relationships.